Corrosion protection of steel cut‐edges by hot‐dip galvanized Al(Zn, Mg) coatings in 1 wt% NaCl: Part I. Experimental study. Issue 5 (28th December 2018) - Dolgikh, Olga; Simillion, Hans; Lamaka, Sviatlana V.; Bastos, Alexandre C.; Xue, Huibin B.; Taryba, Maryna G.; Oliveira, Andre R.; Allély, Christian; Van Den Bossche, Bart; Van Den Bergh, Krista; De Strycker, Joost; Deconinck, Johan
Abstract : Corrosion of AlZnMg coated steel in chloride media is a complicated process, which progress is determined not only by the electrode reactions but also by the local pH and formation of soluble and insoluble corrosion products. In order to adequately describe and predict the corrosion behavior of steel/AlZnMg cut‐edge, a multi‐ion transport, and reaction model (MITReM) is built. Such model takes into account the transport of species in the solution together with their production/consumption in electrochemical and chemical reactions. The main aim of this work is the validation of a numerical model for describing and predicting corrosion of steel/AlZnMg cut‐edge in immersed conditions. This first part describes the experimental work done to obtain model input parameters and validation measurements. The metallic coatings are characterized experimentally with respect to their composition and microstructure, global and local electrochemical behavior (polarization curves, AESEC, and SVET). Local distribution of corrosion products and local pH are also characterized. No blocking effect of the precipitated corrosion products has been observed and dedicated measurements are performed to validate this observation. Based on the experimental input from this part, numerical models of cut‐edge corrosion with different levels of details are developed in Part II. Abstract : A combination of electrochemical and surface analytical techniques is applied to study the corrosion process of cut edges of aluminized steel with different coating alloy compositions. The outcome are qualitative (rate constants, pH distributions, ..) and quantitative (position and composition of corrosion products) insights. The result of this work is used as input for numerical corrosion modelling and validation of simulation results in part II.